Hubungan Asma dan Penyakit Paru Obstruktif Kronis dengan Pneumonia Berdasarkan Rekam Medis - Jackly Parulian; Ervina Rachmawati; Rossalina Adi Wijayanti; Indah Muflihatin (Indonesian Journal Publisher, 2024)
Between 2020 and 2022, there was an increase in morbidity and pneumonia-related deaths at Citra Husada Jember Hospital. This study aimed to analyze the possible association between asthma, chronic obstructive pulmonary disease (COPD), and pneumonia. The research was quantitative with a case-control design. Data were collected from medical records using a checklist sheet. The study population was divided into two groups: the case population included 115 medical records of pneumonia hospitalizations from January to March 2023, while the control population comprised 512 medical records of internal medicine hospitalizations in the same period. A sample size of 89 medical records was selected using simple random sampling. Data were analyzed using univariate techniques for frequency distribution and bivariate methods, such as the Fisher exact test. The results showed a significant association between asthma, COPD, and pneumonia incidence. It was concluded that asthma and COPD are associated with an increased risk of pneumonia. It is recommended that the government and hospitals collaborate to implement the PCV (Pneumococcal Conjugate Vaccine) vaccination program. Individuals with asthma and COPD should undergo regular health assessments and comprehensive treatments, including allergen immunotherapy, to prevent pneumonia-related complications.